ปัจจัยที่ส่งผลต่อประสิทธิภาพในการจัดเก็บภาษีที่ดินและสิ่งปลูกสร้าง ขององค์การบริหารส่วนตำบลศรีสาคร อำเภอศรีสาคร จังหวัดนราธิวาส - ตาเยะ, อิมรอน; ผูหาดา, ฮากีม (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to examine the process used by Sri Sakhon Subdistrict Administrative Organization to encourage citizens to pay land and building tax. The research employed a qualitative approach. Key informants were selected through purposive sampling and included the Mayor, the Chairman of the Subdistrict Administrative Council, the Chief Administrative Officer, the Head of the Finance Division or revenue officers, tax assessment officers, and local residents. Data were analyzed using content analysis. The results showed that the organization promotes tax payment through several communication channels, such as official notification letters, community loudspeaker announcements, coordination with community leaders, and direct follow-up with taxpayers. These efforts help encourage most citizens to cooperate in paying their taxes. In terms of efficiency factors, the findings indicated that: (1) accuracy and completeness are supported by the use of computerized systems and official appraisal values from the Treasury Department, which help ensure correct tax assessment; (2) cost-effectiveness is achieved because the revenue collected is higher than the operational expenses, and the organization has reduced costs by increasing the use of online systems; (3) tax collection generally meets or exceeds the set targets in some fiscal years; and (4) timeliness is supported by a clear and systematic follow-up process for delinquent taxpayers.